2021
DOI: 10.1108/jcm-02-2020-3661
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perceived interactivity and perceived value on mobile app stickiness: an emerging economy perspective

Abstract: Purpose The purpose of this paper is to ascertain the determinants of mobile app stickiness (MASS) in emerging economies. Design/methodology/approach The study proposes a research model about how perceived interactivity (PI), perceived value, flow and self-efficacy influence MASS. The proposed model is then assessed in partial least square structural equation modeling using a survey sample of 587 mobile app users in India. Follow-up in-depth interviews are conducted to corroborate with statistical findings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 75 publications
1
18
0
Order By: Relevance
“…competition and substitute products) increase, the firm could strategically and tactically handle those challenges. However, if Piaggio Ape faces regulatory compliance issues, especially in developing countries where norms are fluid and public-private participation is unstable, it may find those issues hard to tackle (Balasubramanian et al, 2008;Zhu and Sardana, 2020;Nandi et al, 2021). In this study, we found that one of the key reasons for Ape's success can be attributed to its engine emission levels which were far superior to India's emission regulations (i.e.…”
Section: Enabling Local Cluster Development (Creating Shared Value St...mentioning
confidence: 79%
“…competition and substitute products) increase, the firm could strategically and tactically handle those challenges. However, if Piaggio Ape faces regulatory compliance issues, especially in developing countries where norms are fluid and public-private participation is unstable, it may find those issues hard to tackle (Balasubramanian et al, 2008;Zhu and Sardana, 2020;Nandi et al, 2021). In this study, we found that one of the key reasons for Ape's success can be attributed to its engine emission levels which were far superior to India's emission regulations (i.e.…”
Section: Enabling Local Cluster Development (Creating Shared Value St...mentioning
confidence: 79%
“…(5) Self-efficacy and responsiveness Responsiveness increases consumers' enjoyment of mobile commerce (Yang et al, 2017). Besides, responsiveness resolves information requirements (Nandi et al, 2021). Thus, higher responsiveness could result in increased M-Payment adoption.…”
Section: Ijqrm 408mentioning
confidence: 99%
“…Nandi et al (2021) revealed that the perceived interactivity of a mobile app increased mobile app stickiness through utilitarian value and flow. Kim and Baek (2018) demonstrated that a mobile app's interactivity increased app engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the digital age, people are spending more time on their smartphones. Interactive mobile apps have been shown to foster better engagement among users compared to traditional methods of organizational communication (Kim et al, 2013; Nandi et al, 2021). Indeed, crisis mobile apps were utilized during the COVID‐19 pandemic to provide instruction and help users locate critical facilities (Paek & Hove, 2021).…”
Section: Introductionmentioning
confidence: 99%